Investasi Syariah Melalui Surat Berharga Syariah Negara - Mira Misissaifi; Erlindawati Erlindawati (LPPM ISNJ Bengkalis, 2019)
Investment is something that aims to develop the assets owned by expecting high returns. Basically investment in a sharia perspective is an active form of Sharia Economy. Although many investment products have the opportunity to provide high returns, it must be borne in mind that they are solely in the form of worldly benefits but also ukhrawi profits. One form of sharia investment is Sukuk issued by the state in 2008 to expand alternative sources of funding for the State Budget and Expenditure, as well as developing the Islamic Finance market. From the results of the issuance of the State Sukuk, the construction of various infrastructure projects in all corners of the country has now been realized, such as railroad tracks, roads and bridges, revitalization of the hajj hostel, and universities.